Cell Phone Theft and IMEI Manipulation: Detection,Prevention, and Legal Implications (International Journal of Advanced Digital Systems and Multidisciplinary Studies, 2026)
This paper explores the multifaceted issues surrounding cellphone theft and the illicit manipulation of InternationalMobile Equipment Identity numbers, which serve as uniqueidentifiers for mobile devices. The International MobileEquipment Identifier is a critical component for identifyingmobile devices globally, akin to a serial number, and isfactory-assigned, stored in the device's firmware, andtransmitted during network authorization. Despite itsintended permanence, the IMEI can be illegally altered orcloned, facilitating the resale of stolen devices andcomplicating efforts to track and recover them. This paperdelves into the technological vulnerabilities that enablesuch manipulation, the sophisticated methods employed byperpetrators, and the consequential challenges faced by lawenforcement and network providers in combating thisevolving threat. Furthermore, it examines the currentstrategies for detection and prevention, including the roleof centralized databases like the Central Equipment IdentityRegister in blacklisting stolen devices and the continuousefforts by manufacturers to enhance tamper-proof IMEIstorage. The discussion extends to an analysis of the legalframeworks and international collaborations aimed atmitigating the impact of cell phone theft and IMEImanipulation, offering insights into policy gaps andpotential areas for reform.
Keywords: Cell phone theft, IMEI manipulation, mobile security, legal implications, crime prevention.